The soul of creativity forging a moral rights law for the United States - Kwall, Roberta Rosenthal, 1955- (Stanford, Calif. : Stanford Law Books, 2010)
In the United States, human creativity is historically understood to be motivated by economic concerns. However, this perspective fails to account for the reality that human creativity is also often the result of internal motivations having nothing to do with money. This book addresses what motivates human creativity and how the law governing authors' rights should be shaped in response to these motivations. On a practical level, it illustrates how integrating a fuller appreciation of the inspirational dimension of the creative process will allow us to think more expansively about legal protections for authors.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Copyright -- Moral rights -- United States; Authors -- Legal status, laws, etc. -- United States; Creation (Literary, artistic, etc.); Law; United States of America, USA; Intellectual property law